1999
DOI: 10.1038/sj.onc.1202631
|View full text |Cite
|
Sign up to set email alerts
|

Neuregulin-4: a novel growth factor that acts through the ErbB-4 receptor tyrosine kinase

Abstract: The ErbB/HER family of receptor tyrosine kinases consists of four receptors that bind a large number of growth factor ligands sharing an epidermal growth factor-(EGF)-like motif. Whereas ErbB-1 binds seven di erent ligands whose prototype is EGF, the three families of neuregulins (NRGs) activate ErbB-3 and/or ErbB-4. Here we characterize a fourth neuregulin, NRG-4, that acts through ErbB-4. The predicted pro-NRG-4 is a transmembrane protein carrying a unique EGF-like motif and a short cytoplasmic domain. A syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

5
209
0

Year Published

2000
2000
2007
2007

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 281 publications
(214 citation statements)
references
References 59 publications
(61 reference statements)
5
209
0
Order By: Relevance
“…In previous work on NRG4 expression in breast cancer, we observed using reverse transcription (RT)-PCR additional NRG4 mRNA products (Dunn et al, 2004). Here we characterize two of these variants which both posses transmembrane sequences; the previously described NRG4 variant described by Harari et al (1999) which we designate NRG4A1 and a novel 270 bp transcript designated as NRG4A2.…”
mentioning
confidence: 90%
See 4 more Smart Citations
“…In previous work on NRG4 expression in breast cancer, we observed using reverse transcription (RT)-PCR additional NRG4 mRNA products (Dunn et al, 2004). Here we characterize two of these variants which both posses transmembrane sequences; the previously described NRG4 variant described by Harari et al (1999) which we designate NRG4A1 and a novel 270 bp transcript designated as NRG4A2.…”
mentioning
confidence: 90%
“…It is unclear therefore how NRG4 is inserted into the membrane and how the ectodomain is shed (as is the case for some NRG1 isoforms, Wakatsuki et al, 2004) to produce an ErbB4 receptoractivating ligand. Harari et al (1999) who reported the first sequence of NRG4 showed that a refolded peptide representing the EGF domain of mouse NRG4 stimulated the phosphorylation of HER4 and the downstream second messenger protein mitogen-activated protein kinase.Extensive alternative mRNA splicing and the use of at least six sites of initiation of transcription in NRG1 allows the production of more than 15 variants (Harrison and Law, 2006). NRG2 is also alternatively spliced to produce a and b variants (Yamada et al, 2000), and recently isoforms of NRG3 have been described (Carteron et al, 2006).…”
mentioning
confidence: 99%
See 3 more Smart Citations